Visitor perceptions towards forest resorts in Kashmir - M M Kachroo; S H Baba; Arshad Bhat (Agricultural Economics Research Review, 2023)
Forests in the Kashmir valley attract hundreds of thousands of tourists annually. This study uses a trip generation function to analyse the perceptions of a random sample of 200 visitors to four famous forest sites: Dodhpathri, Thajiwas, Pahalgam, and Gulmarg. Forest-specific attributes and ecological/scenic concerns attract tourists, mostly from Kashmir and also from elsewhere in India and abroad. Most tourists are highly educated, well off businesspeople or professionals in the 50–60 age group who consider that forest sites are a national treasure that should be preserved sustainably.